The PISA Report: Equity in the Education System - Tovar Sánchez , Carmen (Avances en Supervisión Educativa, 2025)
PISA is an international programme promoted by the OECD that assesses the key competencies of 15-year-old students every three years, with an emphasis on how they apply their knowledge in real-life contexts. The study analyzes not only the academic performance of participating countries, but also other elements, such as equity, which are key to achieving a quality education system. This paper will describe how PISA analyzes educational equity from the perspective of inclusion (access and minimum performance) and justice (influence of socioeconomic background, gender, or immigration status). Furthermore, this paper explores the policies and structures that countries can develop in their education systems to promote equity, such as access to quality early childhood education, the development of socio-emotional competencies, and the professional development of teachers. It also examines those that hinder equity, but remain common practices in many countries, such as grade repetition or segregation.